(untitled) (International Journal of Occupational Safety and Health, 2022)
Introduction: Mercury is a highly toxic and persistent contaminant found in food and parts of the environment. Over the years, global research on mercury poison has soared owing to concerns about its effects on human health, occupational safety, and environmental sustainability. Although numerous studies have identified and examined the various types, sources, toxicity, exposure, and impacts of mercury, comprehensive studies on the research landscape and scientific developments on the subject areas are currently lacking. Therefore, this paper shows a bibliometric analysis (BA) and literature review (LR) of the top publications, funders, organisations, and countries working on Mercury research worldwide. Methods: The research landscape on the subject area was examined by BA from 1995 to 2021, whereas the scientific developments were highlighted through LR. Results: Results showed that mercury research has gained global prominence since the discovery of the Minamata disease in 1956. The most prolific mercury researchers, institutions, and funders are from the United States, Japan, Brazil, Canada, and China, whereas the publications on Mercury research doubled over the period. The top source titles for publications on Mercury are Neurotoxicology, Science of the Total Environment, and Environmental Health Perspectives. However, Micheal Aschner (US) and Takashi Yorifuji (Japan) are the most prolific researchers. Co-occurrence analysis revealed that mercury, methyl mercury, fish, toxicity, and Minamata disease are the most cited keywords, which shows the correlation nexus between fish consumption and mercury poisoning. Conclusion: The LR showed that mercury research is widely investigated due to global concerns about its impact on human health, safety, and the environment.